2009
DOI: 10.1177/1076029609351877
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Clinical Model Composed of ECG, Shock Index, and Arterial Blood Gas Analysis for Predicting Severe Pulmonary Embolism

Abstract: Adding the scores obtained from SI and ABG to the sECG enhances the specificity of sECG in predicting RVD (+) or severe PE patients, although a lesser degree decreasing in sensitivity may occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…These results confirm other studies that showed arterial blood gas or its combination with other data could not be used to detect PTE, and if used alone, may lower the sensitivity and specificity 20,21…”
Section: Discussionsupporting
confidence: 88%
“…These results confirm other studies that showed arterial blood gas or its combination with other data could not be used to detect PTE, and if used alone, may lower the sensitivity and specificity 20,21…”
Section: Discussionsupporting
confidence: 88%
“…19 Furthermore, sinus tachycardia may be more common in patients with acute PE than chronic PE (74% vs 51%, P = 0007), 45 as well as in pulmonary trunk embolism than peripheral embolism (100% vs 30%), though statistical significance was not calculated for the latter. 46 In terms of prognostication, sinus tachycardia has been shown to be more prevalent in patients with massive PE than nonmassive PE in one study (36% vs 0%), 37 but this finding was not replicated by Bircan et al 42 While some studies have shown that patients with sinus tachycardia are at increased risk of in-hospital complications (88% vs 19%, P = 0.0003; 65% vs 38%, P < 0.05) 38,41 and in-hospital death (91% vs 37%, P < 0.001), 41 several studies have found no significant association with either, 23,38,45 , nor with degree of cardiac biomarker elevation. 47 It appears as though more studies have assessed the prognostic role of atrial arrhythmias and tachycardia "not-further-specified" in the setting of PE rather than sinus tachycardia alone.…”
Section: Updated Evidence On the Value Of Ecg As A Prognostic Tool Ecmentioning
confidence: 92%
“…Sinus tachycardia has been found to be more common in patients with RVD than those without RVD (50% vs 16%, P = 0.012; 55% vs 29%, P < 0.05; 58% vs 21%, P = 0.002), 15,41,44 but was not found to be significant in multivariate logistic regression analysis, 44 and only a trend toward significance was found by Bircan et al (69% vs 31%, P = NS). 42 Sinus tachycardia has also been found to be more common in patients with RV enlargement than those without (29% vs 18%, P = 0.02). 19 Furthermore, sinus tachycardia may be more common in patients with acute PE than chronic PE (74% vs 51%, P = 0007), 45 as well as in pulmonary trunk embolism than peripheral embolism (100% vs 30%), though statistical significance was not calculated for the latter.…”
Section: Updated Evidence On the Value Of Ecg As A Prognostic Tool Ecmentioning
confidence: 95%
See 1 more Smart Citation
“…Shock index (SI), the ratio of heart rate to systolic blood pressure, has been found to predict shock in both settings, primarily in adult populations. Elevated SI, even in the context of normal systolic blood pressure, is associated with shock in multiple conditions including trauma [1][2][3][4], pulmonary embolism [5], pneumonia [6], and ectopic pregnancy [7][8][9]. Elevated SI has also been shown to predict mortality [2,6,10,11] and need for critical care [10,[12][13][14][15][16] in adults.…”
Section: Introductionmentioning
confidence: 96%